Medical ethics during war - Imtiaz Gulamali (Journal of the Pakistan Medical Association, 2025)
As the year’s end, and the New Year of 2025 begins I havereflected upon the role of medics during any conflict andwar. This year, we have yet again witnessed the death andinjuries of thousands of innocent victims of the conflict,raging in different parts of the world like in Palestine,Lebanon, Sudan and Ukraine. Sadly, it is undeniable thatmankind has been involved in conflict in one form oranother for a long time. Although the first recorded largescalewar is believed to date back to 3100 BCE known asthe Battle of Hamoukar,1 skeletons with signs of traumahave been found in prehistoric burial sites like JebelSahaba dating back to 12000 BCE.2 So conflict and warseem to be deeply embedded in human history. Continue...